Integrated Reporting: The Case of Intangible Capital Information - A. A. Ousama (Australasian Accounting, Business and Finance Journal, 2024)
This paper examines the reporting on intangible capital (IC) in annual reports, focusing on its extent and the trends within integrated corporate reporting. Using a comprehensive reporting index, we found that Qatari listed companies reported IC to an extent of 0.408, on average, from 2008 to 2020. This is a relatively high figure if compared to some earlier studies. External intangible capital demonstrated the highest reporting levels, while human capital had the lowest. Significant differences were observed across various IC categories, with notable increases in total IC, external intangible and human capital reporting, while internal intangible capital reporting decreased over the same period. As Qatar transitions to a knowledge-based economy (KBE), these findings are crucial, highlighting the relative advance in IC reporting among Qatari companies. These insights are valuable for regulatory and professional bodies that are aiming to develop IC reporting guidelines or to adopt the International Integrated Reporting Framework, enabling comprehensive IC information that aids stakeholders to assess company performance and value creation, enhancing transparency and confidence in the capital market. For companies, understanding their IC reporting practices helps to identify strengths and weaknesses to meet stakeholders’ needs better, and to support Qatar's economic transformation into a KBE. This pioneering study employs a comprehensive reporting index to capture a wide range of IC information, contributing significantly to the current IC reporting literature, particularly within the Gulf Cooperation Council context.
Keywords: Integrated Reporting; Intangible Capital; Internal Intangible Capital; External Intangible Capital; Human Intangible Capital; Extent; Trend.